قصص الاطفال بين الواقع والخيال مهدي والقيادة السحرية لليندة عيادي نموذجا - غرنوق، تبر, لكلوكة، منية; لشهب، نور الهدى (Univerity of Eloued, 2022)
القصة عموما فن أدبي يهدف إلى كشف أو غرس مجموعة من الصفات والقيم والمبادئ ،ومنها ترتبط قصص الأطفال .فهي فرع منهاوكل ما يكتب بقصد إمتاع الأطفال وتثقيفهم ،وقصص الأطفال تحتوي على شخصيات وأحداث واقعية وخيالية. مثل موضوع دراستنا قصة "مهدي والقلادة السحرية"،التي تتحدث عن العالم الواقعي والخيالي، بما يحتوي من شخصيات وأحداث أيضا واقعية وخيالية . فهذا الأخير صار نقطة تحول لتصرفات الفتى مهدي وتغييرسلوكهللإيجابي ،كما وجدنا القصة تحتوي على جميع القيم الأخلاقية إيجابية كانت أم سلبية ،التي قد تؤثر على القراء الصغار بمدح التصرف الجيد من القبيح بأسلوب جيد وسلس وواضح وصريح Summarizing The story is generally a literary art that aims to reveal or instill a set of qualities, values and principles, and among them, children's stories are related. It is a branch of it, and it is all that is written with the intent of entertaining and educating children. Children's stories contain real and imaginary characters and events.Like the subject of our study, the story "Mahdi and the magic necklace", which we found talks about the real and imaginary characters and events. The latter became a turning point for the behavior of the boy Mahdi and changed his behavior to positive, and as we found the story contains all moral values, whether positive or negative, which may affect young readers by praising the good behavior from the ugly in a good, smooth,clear and frank manner.
Keywords: قصص الأطفال ، أدب الأطفال ، قصة "مهدي والقلادة السحرية" لليندة عيادي ، الواقع ، الخيال .; children's stories ,children's literature, the story ofbmahdi and the magic necklace, by lindaayadi ,reality, fiction